In search of trut h Augustine, Manichaeism and other gnosticism : studies for Johannes van Oort at sixty - Berg, Jacob Albert van den, 1975-; Oort, J. van (Nag Hammadi and Manichaean Studies, 2011)
This volume in honour of Johannes van Oort, formerly University of Utrecht, presently Professor of Patristics and Gnosticism at the Universities of Nijmegen and Pretoria, and past-President of the International Association of Manichaean Studies (IAMS), brings together a rich variety of studies on Augustine, Manichaeism, and other Gnostic currents, thus reflecting the honorand's research interests. The unique collection is divided into four sections: I. Studies in Augustine: Confessions, Sermons, Letters andamp; De Haeresibus; Augustine on Grace andamp; Pluralism; Augustinian 'Gnosis'; II. Studies in Manichaeism: Origins andamp; Myth; Doctrines andamp; Cult; Diffusion andamp; Art; III. Studies in Manichaeism and Augustine: Doctrines; Polemics andamp; Debates with Manichaean Contemporaries; IV. Studies in 'Other Gnosticism': Gnosticism and 'Apocryphal' Texts; Sources of (Ps.) Hippolytus' Refutatio; the Gospel of Judas; Modern Yesidi Gnosticism. The 35 studies are preceded by an overview of Prof. van Oort's scholarly activities and publications